Money and growth : selected papers of Allyn Abbott Young - Young, Allyn A. (Allyn Abbott), 1876-1929 (Routledge studies in the history of economics, 1999)
This book allows full appreciation of the work of Allyn Young, a central figure in the development of American economic thought. It reprints his most significant contributions and lost works.